[quotation] 'Ok, so we have to move - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'Ok, so we have to move. It s your doing, but we ll go. Just tell us when, will it be a Wednesday afternoon, a Thursday morning?' leader of West African fishing community, discussing the inevitability of sea level rises due to global warming, 1998